‘You decided I am old enough for the transition, but not old enough to have a say?’: Exploring young people’s, parents’, and healthcare providers’ views and experiences of Type 1 Diabetes paediatric to adult healthcare transition in Saudi Arabia - Nada Aljohani; Angus Forbes; Ghufran Daqrashawi; Mette Due-Christensen; Sara Donetto; Mariam Asaad; Vicki Tsianakas (PLoS ONE, 2025)
Background Young people with Type 1 diabetes in Saudi Arabia transition from paediatric to adult care at a culturally defined age of 14, which is younger than the average transition age in Western societies. The aim of this study was to elicit the experiences of young people with Type 1 diabetes, their parents, and healthcare providers in Saudi Arabia as they transitioned from paediatric to adult care. Methods In healthcare, Design Thinking is a human-centred approach that draws on participants’ experiences and perspectives to design and develop interventions, models, or services that meet the needs of stakeholders. This study reports the first inspiration phase of the Design Thinking process. Four parallel exploration workshops were held with pre- and post-transition young people with Type 1 diabetes (n = 12), their parents (n = 8), and healthcare providers (n = 7). Findings Six key themes were identified from the workshops’ data analysis. For young people, the key themes were facing the unknown and preparedness; developing autonomy and recognition as an independent person; and interacting with the adult healthcare team. For parents, the themes were navigating the shift in parental role and involvement in care, interacting with healthcare professionals, and changing support needs. For healthcare providers, the key theme was balancing independence and care approaches. Conclusion The Inspiration phase of the Design Thinking approach provided valuable insights from the healthcare transition experiences of young people with Type 1 diabetes, their parents, and healthcare providers in Saudi Arabia. The generated insights facilitated the identification of areas for interventions in the process’s following phases.